Particles in relativistic MHD jets: I. role of jet dynamics in particle acceleration - Dubey, Ravi; Fendt, Christian; Vaidya, Bhargav (The astrophysical journal, 2023)
Relativistic jets from (supermassive) black holes are typically observed in nonthermal emission, caused by highly relativistic electrons. Here, we study the interrelation between three-dimensional (special) relativistic magnetohydrodynamics, and particle acceleration in these jets. We inject Lagrangian particles into the jet that are accelerated through diffusive shock acceleration and radiate energy via synchrotron and inverse Compton processes. We investigate the impact of different injection nozzles on the jet dynamics, propagation, and the spectral energy distribution of relativistic particles. We consider three different injection nozzles—injecting steady, variable, and precessing jets. These jets evolve with substantially different dynamics, driving different levels of turbulence and shock structures. The steady jet shows a strong, stationary shock feature, resulting from a head-on collision with an inner back-flow along the jet axis—a jet inside a jet. This shock represents a site for highly efficient particle acceleration for electrons up to a few tens of TeV and should be visible in emission as a jet knot. Overall, we find that the total number of shocks is more essential for particle acceleration than the strength of the shocks. The precessing jet is most efficient in accelerating electrons to high energies reaching even few hundred TeVs, with power-law index ranging from 2.3 to 3.1. We compare different outflow components, such as the jet and the entrained material concerning particle acceleration. For the precessing nozzle, the particle acceleration in the entrained material is as efficient as that in the jet stream. This is due to the higher level of turbulence induced by the precession motion.
Gesehen am 01.08.2023